Implementation of Qur’anic Reading and Writing Activities among Seventh-Grade Students at MTs S NU Padang Masiang Barus District Kabupaten Tapanuli Tengah - Nurhikmah Marbun (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
This study explores the implementation of the Qur’anic Reading and Writing Program (QRW) at MTs S NU Padang Masiang, Barus, Central Tapanuli, Indonesia. Employing a descriptive qualitative field approach, the research aimed to (1) describe how QRW is implemented and identify supporting and inhibiting factors. Data were collected over approximately three months through classroom observations of QRW sessions, semi-structured interviews with the school principal, QRW teachers, and seventh-grade students, and documentation review. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing/verification, supported by source and method triangulation as well as member checking to enhance credibility. The findings indicate that QRW is implemented as a compulsory extracurricular activity held three times a week and generally supports students’ Qur’anic literacy and the cultivation of discipline, perseverance, and religious habits. However, program effectiveness is constrained by varied initial student competencies, limited instructional time, and inconsistent family support and religious practices in the surrounding environment. The study argues that strengthening diagnostic assessment, differentiated instruction, teacher capacity building, and school–parent collaboration along with more systematic monitoring and evaluation are essential to optimize BTQ outcomes and to inform the development of contextual Qur’anic learning models in madrasahs.